Kajian Yuridis Terhadap Sistem Peradilan Anak Berdasarkan Asas Keadilan Terhadap Pelaku Tindak Pidana Kekerasaan Oleh Anak (Studi Kota Medan) - Pilliang, Antonius Alexander; Muliadi, Mahmud; Marlina, Marlina (ARBITER: Jurnal Ilmiah Magister Hukum, 2020)
In this research, the problem is whether the Child Criminal Justice System has given Justice to children as perpetrators of violent crime? How law enforcement efforts for children as perpetrators of violence by the Medan Municipal Police Department? How the application of justice principles for children as perpetrators of action Violence especially in Medan? The research method used is the normative juridical method, with the leper approach (library reseacrh) that collects the data source from literature literature. In this research used secondary data source that is by using primary, secondary and tertiary law materials. This research is discussed with qualitative approach that is finding problem which then analyzed with inductive system by using legal theories used. The results of this study indicate that the juvenile justice system contained in law number 11 of 2012 has provided justice for children as perpetrators of criminal acts, only in certain circumstances, the application of the criminal justice system does not provide legal certainty for the victims and the community. Law enforcement efforts for children as perpetrators of violent crime are by applying formal and material criminal law in accordance with the prevailing laws and regulations. The application of the principle of justice for children as perpetrators is adjusted to the position of cases that have been done by applying the criminal justice system of children, even in certain circumstances, the application of diversion in cases of violence perpetrated by the child may be enforced.